The treatment of prednisone in mild diabetic rats: Biochemical parameters and cell response - Machado, Mariana P. R. [UNESP]; Schavinski, Aline Z.; Deluque, Amanda L.; Volpato, Gustavo T.; Campos, Kleber E. (Bentham Science Publishers, 2020)
Background: Limited studies have been carried out with prednisone (PRED) in treatment by glucose intolerant individuals, even in this model the animals presented low blood glucose levels at adulthood, by the high regenerative capacity of β-cell. Objective: The aim was to evaluate the effects of the treatment of PRED in mild diabetes on biochemical and immunological biomarkers. Methods: Rats were randomly divided into four groups: control (C), treated control C+PRED (treatment of 1.25 mg/Kg/day PRED); diabetic DM (mild diabetes) and treated diabetic DM+PRED (treatment with same dose as C+PRED group). Untreated groups received vehicle, adjusted volume to body weight. The treatment lasted 21 days and measured body weight, food and water intake, and glycemia weekly. In the 3rd week, the Oral Glucose Tolerance Test (OGTT) and the Insulin Tolerance Test (ITT) was performed. On the last day, the rats were killed and the blood was collected for biochemical analyzes, leukogram and immunoglobulin G levels. Results: There was a significant decrease in body weight in mild diabetes; however, the treatment in diabetic groups increased food intake, glycemia, and the number of total leukocytes, lymphocytes and neutrophils. On the other hand, it decreased the levels of triglycerides, high-density and very lowdensity lipoproteins. In addition, diabetic groups showed glucose intolerance and mild insulin resistance, confirming that this model induces glucose intolerant in adult life. Conclusion: The results showed that the use of prednisone is not recommended for glucose intolerant individuals and should be replaced in order to not to aggravate this condition.
Keywords: Diabetes; Glucocorticoids; Glycometabolism; Immunosuppressant; Lipometabolism; Prednisone